The Role of Inflation in Moderating the Effect of Investment Decisions and Capital Structure on Company Value - Nabila Putri Utami; Widyastuti; Destari Putri Chaerunnisa; Benny Dhevyanto (Indonesian Journal of Business Analytics, 2024)
The purpose of this study is to ascertain and examine how inflation influences capital structure and investment choices in the real estate and property industries. This study employs a quantitative research design and uses secondary data from the Indonesia Stock Exchange (IDX) and the websites of up to 17 different companies throughout the course of three years, beginning in 2020 and ending in 2022. Eviews 13 was used to process the research data. The study's findings demonstrated that capital structure, which was proxied by the long-term debt to equity ratio, and investment decisions, which were proxied by return on investment, had no discernible effects on the price book value of the company. In the meanwhile, choices on investments can be moderated by inflation. on capital structure's impact on a company's worth, and the findings of this study also suggest that inflation may act as a moderator of the impact of investment choices on a company's worth.